Defining dermal adipose tissue. Issue 9 (September 2014) - Driskell, Ryan R.; Jahoda, Colin A. B.; Chuong, Cheng‐Ming; Watt, Fiona M.; Horsley, Valerie
Abstract Here, we explore the evolution and development of skin‐associated adipose tissue with the goal of establishing nomenclature for this tissue. Underlying the reticular dermis, a thick layer of adipocytes exists that encases mature hair follicles in rodents and humans. The association of lipid‐filled cells with the skin is found in many invertebrate and vertebrate species. Historically, this layer of adipocytes has been termed subcutaneous adipose, hypodermis and subcutis. Recent data have revealed a common precursor for dermal fibroblasts and intradermal adipocytes during development. Furthermore, the development of adipocytes in the skin is independent from that of subcutaneous adipose tissue development. Finally, the role of adipocytes has been shown to be relevant for epidermal homoeostasis during hair follicle regeneration and wound healing. Thus, we propose a refined nomenclature for the cells and adipose tissue underlying the reticular dermis as intradermal adipocytes and dermal white adipose tissue, respectively.